Dynamic interaction between grain boundary and stacking fault tetrahedron. (February 2018) - Zhang, Liang; Lu, Cheng; Tieu, Kiet; Shibuta, Yasushi
Abstract: We utilize molecular dynamics simulations to investigate the dynamic interaction between the grain boundary (GB) and the stacking fault tetrahedron (SFT) in bicrystal copper. The grain boundary can migrate itself under the shear strain and can serve as a sink to remove SFT. The sink efficiency of grain boundaries is sensitive to their structural characteristics. The high-angle GBs can show a great ability to remove SFT even at an extreme low temperature, while the increase of temperature can facilitate the annihilation of SFT at the low-angle GBs. This study reveals a new possible GB-mediated damage healing mechanism of irradiated materials. Graphical abstract: Dynamic interaction of shear-coupled grain boundary motion and the stacking fault tetrahedron.